CALENDAR. (Computer (00189162), 2008)
A calendar of events concerning the IEEE Computer Society for 2008 is presented which includes an international symposium on object/component/service-oriented real-time distributed computing, an international conference on technologies for homeland security and an international workshop on policies for distributed systems and networks.